Advice on assistance and protection from the Scientific Advisory Board of the Organisation for the Prohibition of Chemical Weapons: Part 2. On preventing and treating health effects from acute, prolonged, and repeated nerve agent exposure, and the identification of medical countermeasures able to reduce or eliminate the longer term health effects of nerve agents. (1st February 2019) - Timperley, Christopher M.; Abdollahi, Mohammad; Al-Amri, Abdullah Saeed; Baulig, Augustin; Benachour, Djafer; Borrett, Veronica; Cariño, Flerida A.; Geist, Michael; Gonzalez, David; Kane, William; Kovarik, Zrinka; Martínez-Álvarez, Roberto; et al.
Graphical abstract: Highlights: Work of the Organisation of the Prohibition of Chemical Weapons (OPCW) is outlined. Advice on assistance and protection from OPCW Scientific Advisory Board is provided. Advice addresses medical care and treatment of longer term injuries from nerve agents. Scientific literature on the topics is reviewed and over 130 references included. This advice will better inform toxicologists, medics and emergency responders. Abstract: The Scientific Advisory Board (SAB) of the Organisation for the Prohibition of Chemical Weapons (OPCW) has provided advice in relation to the Chemical Weapons Convention on assistance and protection. We present the SAB's response to a request from the OPCW Director-General in 2014 for information on the best practices for preventing and treating the health effects from acute, prolonged, and repeated organophosphorus nerve agent (NA) exposure. The report summarises pre- and post-exposure treatments, and developments in decontaminants and adsorbing materials, that at the time of the advice, were available for NAs. The updated information provided could assist medics and emergency responders unfamiliar with treatment and decontamination options related to exposure to NAs. The SAB recommended that developments in research on medical countermeasures and decontaminants for NAs should be monitored by the OPCW, and used in assistance and protection training courses and workshops organised through its capacity building programmes.